NEGOSIASI DAN MEMORANDUM OF UNDERSTANDING (MoU) DALAM PENYUSUNAN KONTRAK - Sigit Irianto (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2014)
Negotiation and the memorandum of understanding have become an important element in business contracts, particularly those with high value transactions. Negotiation is the very first step in a contract, followed up with memorandum of understanding. The objective of the negotiations is to bring together two different interests, while the memorandum of understanding is a preliminary agreement that contain basic materials before followed with the very detailed contract composing. There are two views about the negotiations and the memorandum of understanding, that developed countries which embrace either common law or civil law systems already incorporate both systems as the binding legal document, while several other countries (including Indonesia) are still considered them as the non-legally binding document.